Some immunological parameters levels in COVID-19 patients in Al-Muthanna governorate, Iraq - AL-Lebawy, Noor Sami; Nahab, Hedaa M.; Abdulkareem, Aws Z. (Edelweiss Applied Science and Technology, 2025)
Coronavirus disease (COVID-19), caused by SARS-CoV-2, has led to a global pandemic and devastating health crisis. Coronavirus (COVID-19) is associated with severe acute respiratory syndrome (SARS-CoV-2), and the exaggerated immune response resulting from infection with this disease leads to high rates of morbidity and mortality. Activation may have a contribution to disease severity.A case study was carried out in order to find the association between COVID-19, TNF-α, IL-8 and IL-2. The effect of age, sex, smoking, diabetic and hypertention on the level of the studied cytokines were evaluated. Inaddition, the influnce of COVID-19 severity on TNF-α, IL-8 and IL-2 levels were studied. Blood samples were collected from 50 Coronavirus disease (COVID-19) patients who visited of Al-Hussein Teaching hospital and 50 control people, during the period from (May -November 2021). The ages of the patients ranged from (Twenty two years to seventy six years). The serum samples were used in detection of TNF-α , IL-8 and IL-2 by using ELISA test. Then the collected data was analysed using Statistical Package for Social Science (SPSS) program version 11. The results showed that that the most affected age group was (40-60) years old followed by less than 40 years old and more than 60 years old. The numbers of patients were 29, 11 and 10 respectively. Most of COVID-19 patients were male (56 %:28), while the rest cases were females (44%:22). The mean values of the studied cytokines in COVID-19 patients in both sex and all age groups were more than their counter parters in H.C group. The effect of main risk factors for severe and long COVID-19 include age, sex, smoking, presence of comorbidities (diabetes, hypertension) on variations in the level of studied cytokines of the host were found significantly. Moreover, the effect of COVID-19 severity on the studied cytokines was highly significants. The maximum values of cytokines were obtaind in critical degree followed by severe and moderate severity. It is concluded from the study’s results that patients infected with severe SARS-CoV-2 experience increasing proinflammatory tumor necrosis factor-α, interleukin-2 and interleukin-8 that produce signaling the initial phase of cytokine storm. Thus, further studies should be conducted to use the studied cytokines inhibitors as a treatment for COVID-19 patients.